2022
DOI: 10.1038/s41598-022-10493-5
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic use of siderophores and weak organic ligands during zinc transport in the rhizosphere controlled by pH and ion strength gradients

Abstract: Citrate (Cit) and Deferoxamine B (DFOB) are two important organic ligands coexisting in soils with distinct different affinities for metal ions. It has been theorized that siderophores and weak organic ligands play a synergistic role during the transport of micronutrients in the rhizosphere, but the geochemical controls of this process remain unknown. Here we test the hypothesis that gradients in pH and ion strength regulate and enable the cooperation. To this end, first we use potentiometric titrations to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…Minor deviations in final mobilized U compared to ligand-only treatments were found for DFOB and citrate, while the final mobilized U concentration from DPA and HBED were partially inhibited by complexation of Zn (68 and 84% less final mobilized U compared to ligand-only treatments, respectively) (Figure ). These findings align relatively well with the extent to which each ligand binds Zn in the absence of U. , Specifically, the free Zn concentration in solution at pH 7.0 was predicted with PHREEQC for each ligand (1:1 metal-to-ligand ratio) in the current study. Model predictions showed that free Zn concentrations were the lowest for HBED (<2% of final Zn concentration), which had the highest inhibition of U mobilization.…”
Section: Resultssupporting
confidence: 85%
“…Minor deviations in final mobilized U compared to ligand-only treatments were found for DFOB and citrate, while the final mobilized U concentration from DPA and HBED were partially inhibited by complexation of Zn (68 and 84% less final mobilized U compared to ligand-only treatments, respectively) (Figure ). These findings align relatively well with the extent to which each ligand binds Zn in the absence of U. , Specifically, the free Zn concentration in solution at pH 7.0 was predicted with PHREEQC for each ligand (1:1 metal-to-ligand ratio) in the current study. Model predictions showed that free Zn concentrations were the lowest for HBED (<2% of final Zn concentration), which had the highest inhibition of U mobilization.…”
Section: Resultssupporting
confidence: 85%
“…Direct observation and accurate measurements of siderophore dynamics in natural rhizosphere ecosystems are di cult to facilitate due to the inaccessibility of high-resolution in situ techniques and the complexity of natural soil substrates (Northover et al 2022). Consequently, laboratory experiments and geochemical models are commonly used to study trace metal acquisition and transport (Di Bonito, Lofts, and Groenenberg 2018).…”
Section: Introductionmentioning
confidence: 99%